Pengaruh Literasi Perpajakan, Sosialisasi Perpajakan, Dan Digitalisasi Sistem Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Generasi Milenial Di Kota Malang - Aida Rohmawati Romadoni; Untung Wahyudi; Dwi Anggarani (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of tax literacy, tax socialization, and the digitalization of the tax system on individual taxpayer compliance among the Millennial Generation in Malang City. As a tech-savvy and economically productive demographic, Millennials play a strategic role in strengthening the national tax base through improved tax compliance. This research adopts a quantitative approach, utilizing a survey method through questionnaires distributed to 87 respondents—individual taxpayers from the Millennial Generation in Malang who are registered with a Taxpayer Identification Number (NPWP) and have submitted tax reports. The sampling technique used was purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, tax literacy and tax system digitalization have a significant effect on individual taxpayer compliance. Meanwhile, tax socialization does not have a significant partial effect. However, simultaneously, all three independent variables have a significant effect on individual taxpayer compliance. The sampling technique used was purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, tax literacy and tax system digitalization have a significant effect on individual taxpayer compliance. Meanwhile, tax socialization does not have a significant partial effect. However, simultaneously, all three independent variables have a significant effect on individual taxpayer compliance.